Having less and wanting more: an investigation of socioeconomic status and reinforcement pathology - Amanda K. Crandall; Amanda M. Ziegler; Tegan Mansouri; Jalen Matteson; Emily Isenhart; Autum Carter; Katherine N. Balantekin; Jennifer L. Temple (BMC, 2021)
Abstract Background In the United states obesity and socioeconomic status (SES), or one's standing in society based on income, education, and/or occupation, are strongly associated. The mechanisms for this relationship may include having high levels of motivation to get food (reinforcing value of food; RRV) and low levels of inhibitory control (delay discounting; DD) which, when combined, is referred to as reinforcement pathology (RP). We sought to examine the relationships among multiple measures of household SES, RP, and age-adjusted body mass index (zBMI) among adolescents. Methods These data were collected as part of ongoing longitudinal study of risk factors for obesity in 244 adolescents. The adolescents and one parent/guardian had height and weight measured and completed surveys. The adolescents completed an adjusting amount DD task and a computer-based RRV task. Analyses consisted of correlations among measures of SES and RRV, DD, and BMI z-scores. In the case of significant associations, multiple regression models were created with theoretically informed covariates. Results Household income, parent/guardian education, parent/guardian occupation, and food insecurity status were all related to one another. Among the adolescents, a significant portion of the variance in RRV was accounted for by household income after controlling for covariates. For DD, it was parent/guardian education that was most associated after controlling for covariates. Conclusion When low income and low parent/guardian education occur together, there may be an increased risk of RP. Separately, food insecurity was predictive of higher parent/guardian BMI. Future research should continue to explore the effects of low income and parent/guardian education on RP among youth by examining them over time.